2017
DOI: 10.1002/mats.201700045
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Polymer Conformational Structure and Dynamics in Linear and Ring Polyethylene Blends

Abstract: Flory theorem," stating that polymers in the melt are nearly "ideal," [28] in the specific sense that they should have similar excluded volume (EV) interactions as polymers at their theta point, i.e., ν = 1/2, simply does not hold for ring melts. Instead, ν for ring melts has often been reported to be near 2/5 [11,12,21,24] which is consistent with the theoretical estimate of Cates and Deutsch. [29] Recent computational studies [16][17][18]30,31] have suggested that very long rings in the melt should be in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 64 publications
6
33
0
Order By: Relevance
“…We emphasize that this asymptotic large mass scaling of RgMnormalw1/2 has only been established for linear polymer chains . Recent simulation and experimental work has indicated that Rnormalg for unknotted rings scales with polymer mass with a power of approximately 1/3 with increasing polymer mass [51,52,53]. This scaling would imply that p should diverge to infinity as Mw for polymers having this non-linear molecular topology.…”
Section: Resultsmentioning
confidence: 99%
“…We emphasize that this asymptotic large mass scaling of RgMnormalw1/2 has only been established for linear polymer chains . Recent simulation and experimental work has indicated that Rnormalg for unknotted rings scales with polymer mass with a power of approximately 1/3 with increasing polymer mass [51,52,53]. This scaling would imply that p should diverge to infinity as Mw for polymers having this non-linear molecular topology.…”
Section: Resultsmentioning
confidence: 99%
“…Blending rings with linear chains produces even more intriguing viscoelastic behaviors due to the interplay of arXiv:2107.01491v1 [cond-mat.soft] 3 Jul 2021 their distinct topologies. The closed-loop structure of rings enables them to be threaded by other chains [19,20,21,22,23,24,25,26,27], which can significantly alter chain conformations [28,29,30], segmental dynamics [19,12,31,32], and blend viscosity [33,34,21,35]. Roovers showed for ring-linear blends of polybutadiene with approximately 15.3 entanglements per chain that there was a maximum in zero-shear viscosity for a ring fraction φ R ∼ 0.4 [36].…”
Section: Introductionmentioning
confidence: 99%
“…These analysis enable us to directly quantify and visualize the flow-driven unthreading of rings from the linear network during elongation. While prior simulation studies have separately characterized some of these quantities for different ring-linear systems [47,23,30,43,32], these results are difficult to aggregate due to variations and limitations in system size, concentration, polymer size, and the degree of ring-linear threading. Thus, in order to build a fuller and clearer picture of topological threading in ring-linear blends, we have generated systems of well-entangled chains with system sizes that are a factor 5-10 times larger than typically found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Although the change of size within the considered interaction range is small its overall effect on the domain size is significant as indicated by the significant shift in the peak position of S(q). Note that the swelling of ring polymers upon addition of small molecules/solvents and linear polymers in the case of homopolymers has been observed in earlier studies, [15][16][17] however it is reported that the nature of swelling is not clear. And in a recent study by Jeong and Douglas it is shown that the swelling arises from altered self-excluded volume interactions which amplifies in the entangled regime.…”
Section: B Chain Conformationsmentioning
confidence: 80%
“…For example, sufficiently long ring polymers are shown to behave as compact object (i.e., size ∼ N 1/3 with N chain length), also unexpected power-law stress relaxation is observed in entangled ring polymers, [8][9][10][11] and smaller diffusion coefficient [12]. Interesting observations are made in case of ring-linear blends, e.g., it shows enhancement of miscibility due to the topological entropy gain of rings upon mixing with linear chains, [13,14] swelling of rings and unusual dynamics of rings in the matrix of linear chains, [15][16][17] and dramatic increase of viscosity of linear melts by adding rings [18]. Recent efforts in understanding the equilibrium and out-of-equilibrium properties of ring * slenin2001@gmail.com polymers focus mainly on homopolymers.…”
Section: Introductionmentioning
confidence: 99%